สำนักงานข้าหลวงใหญ่ผู้ลี้ภัยแห่งสหประชาชาติ กับการเข้าร่วมแก้ไขปัญหา ผู้หลบหนีภัยจากการสู้รบตามแนวชายแดนไทย-พม่า - สถิรกาญจน์ วัชรคุปต์ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
This thesis focused on the United Nations High Commissioner for Refugees participation in solving the problems of Burmese displaced persons fleeing from fighting along the Thai-Burmese border. However, the main objective of this thesis is to study the pressure from international community on the Thai government to allow the UNHCR s participation. This study employed the concept of human rights protection under the United Nations as a framework of analysis. The study found that Thailand has been swamped with Burmese displaced persons fleeing from fighting since 1984. In solving this problem, the Thai government provided temporary shelters along the Thai-Burmese border and allowed non-governmental organizations to give as much assistance as it is permitted under the humanitarian principle. In 1998, Thailand did allow the UNHCR to participate in solving the problem due to pressure from the international community which accused the Thai government for being inhumanely treated the Burmese displaced persons. The international community also urged the Thai government to allow the UNHCR to have a role. Eventually the Thai government accepted the UNHCR s participation as it believed that the UNHCR could witness its transparent operation. The Thai government also wanted to show the UNHCR that is still adherrf to the principle of human rights under the UN charter and other agreements which Thailand was the signatory party.